A Multicenter Noninferiority Study Comparing Safety and Effectiveness of Hyaluronic Acid Fillers for Correction of Nasolabial Folds in Chinese Subjects - Li, Wenzhi; Li, Bi; Hofmann, Matthias; Klein, Gudrun; Xie, Hongfu (Plastic and reconstructive surgery. Global open, 2023)
Hyaluronic acid fillers are the preferred choice for minimally invasive facial volume restoration. In this study, a split-face design was used to compare the effectiveness and safety results of Belotero Balance Lidocaine (BEL) and Restylane (RES, control) to investigate whether BEL is noninferior compared with RES in nasolabial fold (NLF) correction. This was a prospective, controlled clinical study in Chinese subjects. Subjects with symmetrical moderate NLFs according to the Wrinkle Severity Rating Scale were randomized to receive BEL in one NLF and RES in the other. The primary objective was to investigate whether BEL is noninferior compared with RES after being injected mid-dermally in moderate NLFs after 6 months. Secondary objectives included responses at other visits and pain sensation. Treatment-emergent adverse events (TEAEs) were assessed. A total of 220 subjects were enrolled. The Wrinkle Severity Rating Scale response rates at month 6 were 62.9% for BEL versus 64.9% for RES, demonstrating noninferiority. The secondary endpoints supported this. Significantly reduced pain scores were observed for BEL versus RES. For both products, injection site nodule and bruising were the most frequent treatment-emergent adverse events at the injection site. All treatment-related treatment-emergent adverse events were mild. The study showed that BEL is effective and well tolerated for correction of moderate NLFs in Chinese subjects. Noninferiority of BEL was demonstrated compared with RES, and regardless of applied pain treatment, a further reduction in injection pain was observed in BEL.